Medicinal Herbs with Potential Anti-Hypertensive Properties: A Systematic Review of Human and Animal Studies - Maryam Isari; Nazli Namazi; Mohammad Hossein Ayati; Roja Rahimi (Tehran University of Medical Sciences, 2019)
Blood pressure is one of the vital signs, and is the pressure of circulating blood on the walls of blood vessels. When the large arteries lose their natural elasticity and strength, and the smaller ones are narrowed, blood pressure rises and the pressure is exerted by blood on the walls of blood vessels. High blood pressure is dangerous and very harmful for the heart and blood vessels, and is a major cause of mortality in all nations. Many patients tend to use herbal products for controlling their blood pressure, as they are concerned of the side effects of the chemical drugs. There are huge amount of research work exploring the safety and efficacy of a single herb, or combined herbal products on lowering blood pressure, among which some have shown certain effects, and some are negative in results. Grape seed, Garlic, Saffron, Green and White Mulberry, Quince, and some other herbs have more scientific evidence in lowering blood pressure. In this study, we systematically reviewed the scientific literature of clinical trials and animal studies, in which the safety and effectiveness of herbs on lowering blood pressure were evaluated.